Proliferating cell nuclear antigen (PCNA) activity in hepatocellular carcinoma, benign peri-neoplastic and normal liver - Mun, K.S.; Cheah, P.L.; Baharuddin, N.B.; Looi, L.M. (2006)
Hepatocellular carcinoma (HCC) is among the ten most common cancers in Malaysian males. As cellular proliferation is an important feature of malignant transformation, we studied the proliferation pattern of normal and benign perineoplastic liver versus hepatocellular carcinoma in an attempt to further understand the tumour transformation process. 39 HCC (21 with accompanying and 18 without cirrhosis) histologically diagnosed at the Department of Pathology, University of Malaya Medical Centre between January 1992 and December 2003 were immunohistochemically studied using a monoclonal antibody to PCNA (Clone PC10: Dako). 20 livers from cases who had succumbed to traumatic injuries served as normal liver controls (NL). PCNA labeling index (PCNA-LI) was determined by counting the number of immunopositive cells in 1000 contiguous HCC, benign cirrhotic perineoplastic liver (BLC), benign perineoplastic non-cirrhotic (BLNC) and NL cells and conversion to a percentage. The PCNA-LI was also expressed as Ojanguren et al’s grades. PCNA was expressed in 10% NL, 38.9% BLNC, 76.2% BLC and 71.8% HCC with BLNC, BLC and HCC showing significantly increased (p<0.05) number of cases which expressed PCNA compared with NL. The number of BLC which expressed PCNA was also significantly increased compared with BLNC. PCNA-LI ranged from 0-2.0% (mean=0.2%) in NL, 0-2.0% (mean=0.3%) in BLNC, 0-3.6% (mean=0.7%) in BLC and 0-53.8% (mean=7.6%) in HCC with PCNA-LI significantly increased (p<0.05) only in HCC compared with BLC, BLNC and NL. Accordingly, all NL, BLC and BLNC showed minimal (<5% cells being immunopositive) immunoreactivity on Ojanguren et al’s grading system and only HCC demonstrated immunoreactivity which ranged up to grade 3 (75% of cells). From this study, there appears to be a generally increasing trend of proliferative activity from NL to BLNC to BLC and HCC. Nonetheless, BLNC and BLC, like NL, retained low PCNA-LI and only HCC had a significantly increased PCNA-LI compared with the benign categories. This is probably related to the malignant nature of HCC and may reflect the uncontrolled proliferation of the neoplastic hepatocytes.